Local public goods as perfect substitutes – centralization vs. decentralization - Carl Maier (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The main message of recent evaluations of decentralization efforts around the world is that these efforts were unable to generate the beneficial effects they were thought to induce. This finding constitutes a contrast to the rich body of literature on centralization and decentralization which was itself one driving factor of these efforts of decentralization. By arguing that (local) public goods can be viewed as perfect substitutes, this paper provides an explanation for these recent empirical findings and helps to reintegrate them into the theoretical literature on the subject. The main finding of this paper is that centralized and decentralized structures can induce identical provision levels of public goods. This ambivalence is generated by the interaction between electorates and representatives. Whereas both of these actors behave differently in the two scenarios, the overall outcomes are identical due to the leveling effects of strategic delegation. This finding is robust with respect to the assumption of a multistage government.
Keywords: H41; H77; C72; 330